2007
DOI: 10.1107/s0108270107019506
|View full text |Cite
|
Sign up to set email alerts
|

Ring opening of pyridines: the pseudo-cisand pseudo-transisomers of tetra-n-butylammonium 4-nitro-5-oxo-2-pentenenitrilate

Abstract: The reaction of 2-chloro-5-nitropyridine with two equivalents of base produces the title carbanion as an intermediate in a ring-opening/ring-closing reaction. The crystal structures of the tetra-n-butylammonium salts of the intermediates, C(16)H(36)N(+).C(5)H(3)N(2)O(3)(-), revealed that pseudo-cis and pseudo-trans isomers are possible. One crystal structure displayed a mixture of the two isomers with approximately 90% pseudo-cis geometry and confirms the structure predicted by the S(N)(ANRORC) mechanism. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…It has been established from earlier studies that in the absence of high concentrations of hydroxide ions, the intermediate 4 is a somewhat more stable and long‐lived anion. The NMR and x‐ray crystallographic studies by Zeller et al confirm the structure 4 , predicted by S N (addition of the nucleophile, ring opening and ring closure) mechanism. They observed that the negative charge is highly delocalized, but relatively small differences in C–C bond distances indicate a system of conjugated double bonds with the nitro group bearing the negative charge.…”
Section: Introductionmentioning
confidence: 65%
“…It has been established from earlier studies that in the absence of high concentrations of hydroxide ions, the intermediate 4 is a somewhat more stable and long‐lived anion. The NMR and x‐ray crystallographic studies by Zeller et al confirm the structure 4 , predicted by S N (addition of the nucleophile, ring opening and ring closure) mechanism. They observed that the negative charge is highly delocalized, but relatively small differences in C–C bond distances indicate a system of conjugated double bonds with the nitro group bearing the negative charge.…”
Section: Introductionmentioning
confidence: 65%
“…The mechanism of this reaction has been reported (El- Bardan, 1999). With 2-chloro-5-nitropyridine, additional hydroxide base should not be used as the compound undergoes ring opening Zeller et al, 2007).…”
Section: S1 Commentmentioning
confidence: 99%
“…For the mechanism of the reaction between 2-chloro-5-nitropyridine and aryloxide ions, see: El-Bardan (1999); ; Zeller et al (2007). = 76.020 (3) V = 149.50 (6) Å 3 Z = 1 Mo K radiation = 0.56 mm À1 T = 100 K 0.45 Â 0.15 Â 0.03 mm…”
Section: Related Literaturementioning
confidence: 99%